Phase- and morphology-controlled synthesis of tunable plasmonic MoO3-x nanomaterials for ultrasensitive surface-enhanced raman spectroscopy detection - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Mukherjee, Shatabdi Porel (Journal of Physical Chemistry C, 2020)
The enhancement of the surface-enhanced Raman scattering (SERS) property of the plasmonic metal oxide semiconductor nanostructures by controlling their phase, shape, size, and oxygen vacancy to detect trace amounts of organics is of significant interest. In this study, a simple surfactant-free hydrothermal strategy was proposed to fabricate crystalline h-MoO3-x and alpha-MoO3-x nanomaterials with tunable plasmonic properties. Herein, the crystal phase, morphology, and oxygen vacancy of MoO3-x nanostructures were precisely controlled under suitable synthetic conditions. The plasmonic properties of the as-synthesized h-MoO3-x and alpha-MoO3-x micro-/nanostructures were controlled by adjusting the residual volume in the autoclaving chamber. In addition, the plasmonic MoO3-x exhibited SERS activity with a detection limit as low as 1.0 x 10(-9) M and the maximum enhancement factor (EF) up to 6.99 x 10(5) for h-MoO3-x, while for alpha-MoO3-x, the detection limit was 1.0 x 10(-7) M with the corresponding EF up to 8.51 x 10(3), comparable with plasmonic noble metal nanomaterials without a ``hot spot''.

Scalable mechanochemical synthesis of beta-ketoenamine-linked covalent organic frameworks for methane storage - Asokan, Kiran; Patil, Manoj Krishnat; Mukherjee, Shatabdi Porel; Sukumaran, Santhosh Babu; Nandakumar, T. (Chemistry-An Asian Journal, 2022)
In the current scenario of increased pollution and releasing toxic gases by burning petroleum products, switching to natural gas is more promising for reducing CO2 emissions and air pollutants. Hence, research on Liquefied Natural Gas and Compressed Natural Gas is gaining more value. However, natural gas primarily consists of CH4, which has less energy density than conventional fuels. Interestingly, since the C-H ratio of CH4 gas is 1 : 4, it is easily combustible, gives less carbon footprint, and reduces unburnt hydrocarbon pollution. Hence, research on storing and transporting CH4 has utmost importance, and porous materials are one of the suitable candidates for storing CH4. Herein we report the scalable synthesis of highly porous and crystalline covalent organic frameworks for storing CH4 at room temperature and pressure. Two COFs, namely, Tp-Azo and Tp-Azo-BD(Me)(2), synthesized in 1 kg at similar to 45 g batch scale using a Planetary mixer, displayed a maximum BET surface area of around 3345 m(2)/g, and 2342 m(2)/g and CH4 storage of 174.10 cc/cc and 151 cc/cc, respectively. A comparison of the CH4 sorption of Tp-Azo and Tp-Azo-BD(Me)(2) COFs synthesized in different batches has a variation of only +/- 5 cc/cc and shows the consistency in bulk scale synthesis of COFs. The cyclic equilibrium CH4 adsorption studies showed the COFs are stable with consistent CH4 adsorption and desorption cycles. The present study is a step towards the scalable mechanochemical synthesis of COFs for gas storage applications.
Keywords: CH4 storage; COF; porous material; scalable synthesis

Ligand-free one-pot synthesis of Ru/W18O49 self-assembled hierarchical coral-like nanostructures for selective conversion of glucose into glycols - Patil, Manoj Krishnat; Gaikwad, Supriya Hanmant; Kirali, Arun Arunima Balachandran; Marimuthu, Banu; Mukherjee, Shatabdi Porel (ACS Applied Nano Materials, 2023)
In this study, we report a simple inorganic route for the synthesis of Ru/W18O49 self-assembled coral-like nanostructures, with the following advantages: It is one step and requires no surfactant or stabilizing agent; Ru loading is easily tuned, and the as-synthesized nanomaterials can be used as a catalyst without any further processing. The preliminary investigations of the catalytic performance of these as-synthesized Ru/W18O49 nanomaterials appear quite promising for converting glucose to glycols. The total glycol selectivity of 82.6% with 100% conversion of glucose was obtained over 0.03 wt % Ru loading on tungsten nanostructures, which turns out to be the lowest Ru loading% on support reported to date to achieve the highest total glycol selectivity among the previously reported catalyst based on Ru-nano/composite materials. Additionally, preliminary results show that the concentration of Ru on W18O49 significantly affects the selectivity of the glycol production. Thus, our methodology will open up a wide range of opportunities regarding the choice of metals, stoichiometric/nonstoichiometric WOx (x=1-3) as support, and the viability of further catalytic manipulations. A probable catalytic mechanism for this catalytic process is also proposed.
Keywords: glycols; Nanostructure; One-pot synthesis; ruthenium (Ru); selective conversion of glucose; tungsten oxide (W18O49)

One-step microwave-assisted synthesis of a MoO3-x-covalent organic framework (COF)-based nanocomposite for amplified surface-enhanced Raman spectroscopy in environmental applications - Patil, Manoj Krishnat; Wagh, Premjeet Gangadhar; Mukherjee, Shatabdi Porel (Nanoscale, 2026)
This study introduces a novel one-step microwave-assisted (MW-AT) synthesis strategy for a TpTTA COF and demonstrates the fabrication of a MoO3-x-TpTTA COF-based nanocomposite (NC) for the first time. This method significantly reduces synthesis time (similar to 1 h) while achieving a high yield at a moderate temperature (120 degrees C). In contrast, traditional solution-based COF synthesis methods may take several days with continuous heating at higher temperatures (<= 200 degrees C). The as-synthesized MoO3-x-COF-based NC was shown to serve as an affordable and straightforward substrate for surface-enhanced Raman scattering (SERS) detection of an organic dye, such as methylene blue (MB), achieving a maximum enhancement factor (EF) of 7.76 x 104. The incorporation of MoO3-x into the COF provides several advantages, including plasmonic enhancement by nonstoichiometric transition metal oxide (TMO) without requiring the addition of noble nanocrystals (e.g., Ag, Au, etc.), improved stability of the SERS substrate, comparable SERS sensitivity, and reduced costs. Furthermore, the as-synthesized MoO3-x-TpTTA COF-based SERS substrate demonstrated exceptional detection capabilities with high reproducibility, achieving a limit of detection (LOD) as low as 12.5 ppm for Mancozeb (Mz), a common commercially used dithiocarbamate insecticide used on various vegetables, fruits, nuts, and field crops. Notably, Mz is classified as a category III carcinogen by the International Agency for Research on Cancer. This highlights the potential for developing TMO-COF-based NCs for next-generation SERS-based applications in environmental and food safety monitoring.